2006
DOI: 10.1111/j.1755-0238.2006.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Crop thinning (hand versus mechanical), grape maturity and anthocyanin concentration: outcomes from irrigated Cabernet Sauvignon (Vitis vinifera L.) in a warm climate

Abstract: Crop thinning subsequent to fruit set can help regulate yield and improve fruit composition at harvest. Accordingly, an experiment was established in two vineyards (Site 1 Riverland District of South Australia; Site 2 Sunraysia District of Victoria) to investigate effects of crop removal after fruit set (when berries were pea size) using a machine harvester. Specific zones of the canopy were targeted for thinning to remove a predetermined percentage of the fruit and avoid over‐thinning. Cropping responses to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
82
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 19 publications
(8 reference statements)
12
82
0
1
Order By: Relevance
“…There are positive effects of crop removal, including advanced fruit maturity, decreased acidity, and increased anthocyanins and phenolics in Cabernet Sauvignon (Petrie & Clingeleffer 2006). General increases in berry, must, and wine phenols and anthocyanins from Merlot and Cabernet Sauvignon cluster thinning treatments were confirmed by Di Profio et al (2011a,b) and Mazza et al (1999).…”
supporting
confidence: 65%
“…There are positive effects of crop removal, including advanced fruit maturity, decreased acidity, and increased anthocyanins and phenolics in Cabernet Sauvignon (Petrie & Clingeleffer 2006). General increases in berry, must, and wine phenols and anthocyanins from Merlot and Cabernet Sauvignon cluster thinning treatments were confirmed by Di Profio et al (2011a,b) and Mazza et al (1999).…”
supporting
confidence: 65%
“…Many inconsistent results have been reported (Clingeleffer 2010, Keller et al 2005, Nuzzo and Matthews 2006, Reynolds and Vanden Heuvel 2009. Reducing crop load (either by pruning or cluster thinning) generally reduces yield and increases berry TSS compared to high cropload vines (Chorti et al 2010, Guidoni et al 2002, Ollat and Gaudillere 1998, Petrie and Clingeleffer 2006, Petrie et al 2000, Reynolds et al 1994. Other studies showed that cluster thinning or defoliation has little or no influence on soluble solids at harvest (Keller et al 2005, Nuzzo and Matthews 2006, Tardaguila et al 2010.…”
Section: Sugar Concentrationmentioning
confidence: 99%
“…There are two main strategies: one is to harvest all treatments on the same date (Chorti et al 2010, Guidoni et al 2002, Ollat and Gaudillere 1998, Petrie and Clingeleffer 2006, Petrie et al 2000, Reynolds et al 1994) and the other is to harvest each treatment when a targeted sugar concentration is reached (Bates 2008, Garcia de Cortazar-Atauri et al 2009, Keller et al 2005, Kliewer and Dokoozlian 2005, Nuzzo and Matthews 2006. Almost all studies that reported a significant modification in sugar concentration in response to altered water supply and crop load used the first sampling strategy (Chorti et al 2010, Guidoni et al 2002, Ollat and Gaudillere 1998, Petrie and Clingeleffer 2006, Petrie et al 2000, Reynolds et al 1994. When the second sampling strategy was used, it was shown that water supply and crop load did not affect the final sugar concentration, but did modify the duration of accumulation (Bates 2008, Keller et al 2005, Kliewer and Dokoozlian 2005, Nuzzo and Matthews 2006.…”
Section: Sugar Concentrationmentioning
confidence: 99%
“…(Hunter et al, 1995;Haselgrove et al, 2000;Mateus et al, 2001Mateus et al, , 2002Ojeda et al, 2002;Deloire et al, 2005;Downey et al, 2005;Petrie & Clingeleffer, 2006;Poni et al, 2006;Castellarin et al, 2007;Cortel et al, 2007;Bindon et al, 2008;Holt et al, 2008;Tarara et al, 2008;Hanlin et al, 2009;Chorti et al, 2010;Hunter et al, 2010). Furthermore, these factors may also affect berry size and modify proportions of skin, flesh and seed in the grapevine berry.…”
Section: Introductionmentioning
confidence: 99%